Advent of nanomaterial in modern health science and ayurveda. (2021) - Roopashree, S.; Anitha, J.; Rashmi, S.
Abstract: Nanotechnology, a revolutionary perception for future research deals with extremely minute particles of the size 10 -9 of a meter. Though it was coined in 1974, scientists are methodically focusing to benefit most from nanomaterials and its enhanced qualities. Today, its applications have been flourished in many significant fields such as agriculture, medical sciences, electronics, biotechnology and many more. Nano-health uses Nanomedicine, a fragment of Nanomaterial in health care is very essential as nano drug delivery can minimize the side effects, allows for early detection of diseases, reduce damage to healthy body cells and consumption of drug dosage. Ayurveda is an ancient Indian traditional system of medicine use herbs, metals and non-metals for their medicinal preparations. Incorporating Nano-health in traditional therapy of Ayurveda will certainly eliminate one of the major pitfalls of metal toxic effect in its medicines by converting into biological nanoparticles. An approach of Nanotechnology in general medicine comprises of nanomaterials in delivering drugs, light or heat to specific type of cells in the body. Similarly, several Ayurveda drug dosages are in the form of Bhasma (incinerated metals) – a nanomaterial outcome of several metallic preparations. In this paper, an attempt using Artificial Intelligence approach to cast light on the dominance of nanomaterials on both modern and traditional therapeutics by taking at most care of ecology and environment.